Implementation of Final Exam Registration Information System (SIPUAN) as the Idea of Entrepreneurial Information Technology - Mohammad Idhom; Ronggo Ali (Nusantara Science and Technology Proceedings)
Institutions of higher education in particular have a responsibility in producing graduates who are qualified in the various fields of science. College doing curriculum development as the basis for the student in the educated, in a curriculum there are plans of study that will be evolved by the student. State where students will come undertake final project/Thesis that begins with the submission of the proposal for the appointment of the supervisor, then to carry out the test of the final project/Thesis to the examiners. By doing business in the field of ideas develope TI in particular the development of Final Exam Registration Information System (SIPUAN) with a way to combine multiple components of information systems to build the basic idea of the IT business and meets the specific needs of customers is expected to enhance the potential of the IT product/service in the market and by understanding their needs, then it can fulfill value is customers and with it so will encourage them to continue to purchase products that have been produced.